PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Sebrina Ayu Sari; Andajani Andajani (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
This research examines the effect of capital structure, liquidity, and profitability on the firm value. The capital structure was measured by Debt to Asset Ratio (DAR), liquidity was measured by Current Ratio (CR), and profitability was measured by Return on Assets (ROA). Meanwhile, firm value was measured by Price to Book Value (PBV). The population consists of Food and Beverages manufacturing sub-sector companies listed on the Indonesia Stock Exchange (IDX) during 2022 - 2023. Furthermore, the research applies quantitatively. The data collection technique used was a purposive sampling, with 3 criteria. In line with that, 49 companies fulfilled the criteria as samples with a total of 98 observation data. Moreover, the data were secondary, in the form of annual financial reports from the IDX website or the Indonesia Stock Exchange. The data analysis technique used multiple linear regression. The result shows that capital structure, liquidity, and profitability affect firm value.